Independent aggregation in the nordic day-ahead market: What is the welfare impact of socializing supplier compensation payments? - Kārlis Baltputnis; Tim Schittekatte; Zane Broka (Heliyon)
This paper addresses the participation of independent aggregators (IAs) for demand response (DR) in European electricity markets. An IA is an aggregator trading the flexibility of consumers of which it is not the electricity supplier. Particularly, we focus on the controversial issue of a compensation payment from the IA to the supplier for energy sourcing. Concretely, we explore the potential welfare impacts of partial or full socialization of the compensation payment. For this, a static simulation framework is introduced utilizing historical day-ahead market bid and offer data from the Nordic region to rerun market clearing under different scenarios of compensation rules and with diverse assumptions regarding the DR aggregated by IAs. The overall welfare impacts comprise of changes in producer and consumer surplus, DR consumer welfare impact and the socialized part of the compensation. Based on a case study utilizing data for the full year of 2018, it is found that subsidizing the participation of IAs in the day-ahead market leads to negative overall welfare impacts due to over-incentivization of demand reduction. However, in nearly all investigated cases the socialization of the compensation payment leads to positive impacts on the consumer surplus, driven by reduced electricity wholesale prices. The optimal share of the socialization of the compensation that leads to the highest net consumer benefit depends on many factors, among which the assumptions around activation costs of DR are the most evident. Nevertheless, we argue that the socialization of the supplier compensation should be at least conditional upon the level of the hourly wholesale price (i.e., a “threshold price”) and on DR cost estimates. Only in the case when high shares of untapped DR are relatively cheap, net welfare benefits will result.